2010
DOI: 10.3130/jaabe.9.185
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Analysis Comparison of Different Types of Earthmoving Operations by Means of Various Productivity Measurements

Abstract: Researchers and site engineers in construction have tried to develop appropriate methods of productivity measurements. Even though many methods have been released in academia and industry, they seldom are able to select the optimized method while considering various site conditions. This study was developed from a previous study which presented the quantified productivity differences on one specific operation, that of the conventional earthmoving operation. This study suggested more consistent results for prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A truck, for instance, will be routed to an alternative loading area if the loading unit is under maintenance or trucks are waiting in queue. Each strategy taken in designing the operation will have a direct impact on productivity and cost Han [1], Panas and Pantouvakis [2]. So the importance of using simulation as a tool for accurate planning and estimation of earthwork operations is revealed.…”
Section: Introductionmentioning
confidence: 99%
“…A truck, for instance, will be routed to an alternative loading area if the loading unit is under maintenance or trucks are waiting in queue. Each strategy taken in designing the operation will have a direct impact on productivity and cost Han [1], Panas and Pantouvakis [2]. So the importance of using simulation as a tool for accurate planning and estimation of earthwork operations is revealed.…”
Section: Introductionmentioning
confidence: 99%
“…The CYCLONE methodology has been used in many applications to measure construction productivity [14]. In this study, two simulation models, originally designed by Lee [15], were suggested.…”
Section: Productivity Analysismentioning
confidence: 99%
“…(Han, 2010) The performance-based productivity management techniques for a project provide unreliable outcomes on scheduling for a project's stakeholders since they do not consider the environment of construction work that is interdependent and has various uncertainties (Ballard and Howell, 2003).…”
Section: Introductionmentioning
confidence: 99%